Determining the Main Sizes of Gears to Drive Rubber Sheet Roll Grinding Machines on Speed Roll Rotation on the Roll Machine Unit Sheeter - Sitorus, Fransnazoan; Dejoi Irfian Situngkir; Aji Mirwarna; Nuzuli Fitriadi (LPPM Politeknik Aceh Selatan, 2025)
This research aims to determine the main dimensions of the roll drive gear on the roll rotation speed in the roll sheeter machine. The roll rotation speed influences the quality and efficiency of the milling process to produce Ribbed Smoke Sheet. The results of the research show that the main sizes of gears on the roll sheeter machine are the gear module used is 8.34 mm, the diameter of the stitch is (150.12 mm), the inside diameter is (129.27 mm), the outside diameter is (166.80 mm), tooth height (18.76 mm), circle distance (26.18 mm), tooth width (125.10 mm), and tooth thickness (14.40 mm) and roll rotation speed on the roll sheeter machine (roll-1 =0.45 m/s), (roll-2 =0.49 m/s), (roll-3 =0.53 m/s), (roll-4 =0.57 m/s), (roll-5 =0.68 m/s), and (roll-6 =0.56 m/s).